Transient analysis of attemperator enthalpy balance based on the commissioning data of a coal-fired steam power plant. (5th March 2019) - Uruno, Yumi; Choi, Geunwon; Sung, Minjun; Chung, Jaewon; Kim, Hyojun; Lee, Kihyun
Graphical abstract: Highlights: Control logic for spray water uses thermowell measurements at attemperator outlet. Thus, spray injected steam should be desuperheated before the outlet thermowell. Enthalpy balance in the attemperator using steady-state analysis is not accurate. A transient analysis methodology using a lumped capacitance model is presented. Commissioning data of the attemperator in the steam power plant was analyzed. Abstract: In an attemperator, spray water is injected into superheated steam to control its temperature. Since the temperature measured by the thermowell installed at the attemperator outlet is used for the feedback control of the spray water, it is important that the spray water is completely evaporated before the thermowell. This ensures that the thermowell measures the temperature of desuperheated steam. In this study, measurements from the commissioning test of a coal-fired steam power plant were analyzed using transient analyses. These analyses compensated for delayed temperature measurement at thermowells with large heat capacities and the temperature change of spray water extracted far from the attemperator. By using these results for the enthalpy balance in the attemperator, the spray water flow could be calculated accurately enough to verify whether the spray-injected steam was completely desuperheated before the outlet thermowell or not, even during operations with changing the generator load. Temperature readings from thermowells depend on the subcritical and supercritical conditions and the validity of the various simplifications used in the transient analysis were discussed. According to the transient analysis of the commissioning data, the thermowell distance in one of the attemperators could be judged as being too short to ensure complete desuperheating of the spray-injected steam, and thus, this should be considered in the control logic.